Fecal microbiota transplant promotes response in immunotherapy-refractory melanoma patients - Baruch, Erez N.; Youngster, Ilan; Ben-Betzalel, Guy; Ortenberg, Rona; Lahat, Adi; Katz, Lior; Adler, Katerina; Dick-Necula, Daniela; Raskin, Stephen; Bloch, Naamah; Rotin, Daniil; Anafi, Liat; et al. (Science (American Association for the Advancement of Science), 2021)
The composition of the gut microbiome influences the response of cancer patients to immunotherapies. Baruch et al. and Davar et al. report first-in-human clinical trials to test whether fecal microbiota transplantation (FMT) can affect how metastatic melanoma patients respond to anti–PD-1 immunotherapy (see the Perspective by Woelk and Snyder). Both studies observed evidence of clinical benefit in a subset of treated patients. This included increased abundance of taxa previously shown to be associated with response to anti–PD-1, increased CD8 + T cell activation, and decreased frequency of interleukin-8–expressing myeloid cells, which are involved in immunosuppression. These studies provide proof-of-concept evidence for the ability of FMT to affect immunotherapy response in cancer patients. Science , this issue p. 602 , p. 595 ; see also p. 573 Resistance to immunotherapy can be overcome using fecal microbiota transplantation for patients with metastatic melanoma. The gut microbiome has been shown to influence the response of tumors to anti–PD-1 (programmed cell death–1) immunotherapy in preclinical mouse models and observational patient cohorts. However, modulation of gut microbiota in cancer patients has not been investigated in clinical trials. In this study, we performed a phase 1 clinical trial to assess the safety and feasibility of fecal microbiota transplantation (FMT) and reinduction of anti–PD-1 immunotherapy in 10 patients with anti–PD-1–refractory metastatic melanoma. We observed clinical responses in three patients, including two partial responses and one complete response. Notably, treatment with FMT was associated with favorable changes in immune cell infiltrates and gene expression profiles in both the gut lamina propria and the tumor microenvironment. These early findings have implications for modulating the gut microbiota in cancer treatment.